From Scottish Independence, to Brexit, and Back Again: Orange Order Ethno-religion and the Awkward Urgency of British Unionism. (1st December 2022) - Webster, Joseph
Abstract: The Orange Order is an ultra-Protestant and ultra-British fraternity dedicated to professing 'hostility to the distinctive despotism of the Church of Rome', and to preserving Scotland's constitutional place within the UK. According to Scots-Orangemen, these two commitments are united in opposing Scottish National Party capitulations to a Papacy hell-bent on cleaving Scotland from the UK and her Protestant monarch. Thus, while the 2014 Scottish Independence Referendum posed an existential threat to Orange Protestant-unionism, Brexit allowed push-back against an ultramontane plot to use the EU to destroy British sovereignty. Ironically – and awkwardly – the British unionism of Brexit (which the Order celebrates) looks set to reinvigorate calls for Scottish independence (which the Order dreads). This paper examines the acute political crises that such referendums create, arguing that Orange political urgency can only be understood as part of a more chronic (and thus less urgent, if no less serious) 'Roman' threat to Protestant ethno-religious supremacy. L'Ordre d'Orange est une fraternité ultra-protestante et ultra-britannique qui se consacre à professer son "hostilité au despotisme distinctif de l'Église de Rome" et à préserver la place constitutionnelle de l'Écosse au sein du Royaume-Uni. Selon les Écossais-Orangistes, ces deux engagements s'unissent pour s'opposer aux capitulations du Scottish National Party devant une papauté déterminée à séparer l'Écosse du Royaume-Uni et de son monarque protestant. Ainsi, alors que le référendum de 2014 sur l'indépendance de l'Écosse représentait une menace existentielle pour le protestantisme orangiste, le Brexit a permis de repousser un complot ultramontain visant à utiliser l'Union Européenne (UE) pour détruire la souveraineté britannique. Ironiquement ¬— et maladroitement — l'unionisme britannique du Brexit (que l'Ordre célèbre) semble destiné à revigorer les appels à l'indépendance de l'Écosse (que l'Ordre redoute). Cet article examine les crises politiques aiguës que de tels référendums créent, en soutenant que l'urgence politique de l'Ordre d'Orange ne peut être comprise que comme faisant partie d'une menace "romaine" plus chronique (et donc moins urgente, mais non moins sérieuse) pour la suprématie ethno-religieuse protestante.